Problems, solutions, and strategies for developing stock waqf in Indonesia - Rini, Nova; Huda, Nurul; Anshori, Muslich; Darodjatun, M A S Sridjoko; Zaenudin, Zaenudin; Fofana, Mamady; Harumain, Yong Adilah Shamsul (Jurnal Ekonomi & Keuangan Islam, 2024)
Purpose – This study aimed to determine priority problems, solutions, and strategies for developing stock waqf in Indonesia.Methodology – The analytical method used was qualitative with the Delphi approach. The informants for this research were experts in the field of shared waqf. The group of informants consisted of regulators, sharia stock practitioners, nazhir, academics, and wakif with a total of 13 informants.Findings – The results show that the priority issues regarding investor knowledge are from the wakif aspect. A priority problem is the low-literacy stock waqf. The solution priority is from a regulatory perspective. The sub-criteria of the operating rules that are the priority for the solution are the issuance of technical regulations for managing stock waqf. The strategy priority that can be implemented to develop a stock waqf is from the Nazhir aspect as a human resource. Implications – The implications of the research results are in the form of a strategy implemented by the Indonesian waqf board (Badan Wakaf Indonesia, BWI) by issuing standard operating procedures (SOP) for nazhirs in the management of stock waqfs.Originality – The novelty of this research lies in the development of stock waqf, as seen from the problems, solutions, and strategies. In addition to different things, this study also uses a qualitative Delphi approach to formulate problems, solutions, and strategies for developing equity waqf in Indonesia. The Delphi method has not been widely used in Indonesian stock waqf research.